Why Being a For-Profit in the Non-Profit Sector Makes Sense - Seah, Carolyn (Institutional Knowledge at Singapore Management University, 2008)
In 2007, the Lien Centre for Social Innovation was commissioned by the Ministry of Community Development, Youth and Sports to study the social enterprise space in Singapore for the first time. Carolyn Seah summarises the study’s findings.